In vitro antiflamatory effect and safety on rats of atomized aqueous extract from Krameria lappacea (ratania) root - Femández, Américo (2007)
The objetive has been to determine the antiinflammatory activity in Vitro in red globules of rats and to know the security in rates of the watery extract atomizado of Krameria's lappacea root (ratania), also the marker of oxidativo stress (malondialdehído MDA). The antiinflammatory activity in vitro (Hernández et al. 2006) was in red globules of rat faced 10, 50, 100 and 200 ug/mL of extract, a solution control (distilled water 1 mL) and solution of reference hidrocortisona to 400 ug/mL; the security was realized in albino rats Holtzmann distributed in 3 groups: normal with physiological whey 5 mL/kg, A group with inoculation subcutaneous route of a compound constituted by dietilamina and nitrito of sodium in three mammary glands, and the third in addition to inoculate received 300 mg/kg of the extract administered by oral route to the day for 30 days, then it extracted sample of blood to them by cardiac puncture, being sacrificed by cervical dislocation, the scoreboard of stress decided oxidativo for the method of Buege and Aust (1978) and biochemical parameters. Greater antiinflammatory efficiency was observed when using ratania in concentration of 50 and 200 ug/mL; decrease of the MDA (p < 0.404); total cholesterol (p < 0.003); triglicéridos (p < 0.043); total proteins (p < 0.0001) albumen (p < 0.203); TGO (p < 0.093); TGP (p < 0.023); alkaline Fosfatasa (p < 0.670). It Conclused wath in the experimental conditions there has been demonstrated that Krameria lappacea (ratania) has antiinflammatory activity in vitro.